(untitled) - Dobbs-Higginson, Michael S. (Port Melbourne, Vic., 1993)
Contents: Overview, the principal players of Asia pacific, the arguments and a general blueprint for a regional forum in Asia pacific, epilogue.
Keywords: Asia,Châu Á; Politics and government,Chính trị và chính phủ; 1945-,1945-